Production of Glucoamylase Enzyme - Boncalon, Ma. Roela V.; Kintanar, Nimia Pegasa E.; Lina, Lea M. (Diliman, Quezon City College of Engineering, 1995)
Product: Glucoamylase enzyme - 2000 eu/ml -- Plant location: Laguna - industrial area -- Annual volume of product: 9600 kg -- Annual gross sale: P 17,280,000 -- Annual gross income: P 11,153,561 -- Total capital investment: P 10,196,817 -- Product unit cost: P 639/kg -- Suggested product selling price: P 1,800/kg -- Return on investment: 71.1% -- Payback period: 1.41 years -- Breakeven capacity: 1285 kg
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design
Keywords: Factories -- Design and construction; Agricultural processing plants; Glucans